Optimizing emulsion stability of high-oil pourable dressings using different stabilizers - Grizio, Miranda (Kansas State University, 2011)
To find an optimal formulation of oil-in-water (O/W) emulsion pourable dressings containing 60% and 70% soybean oil, nine stabilizers common to the dressing industry were tested, each at three concentrations. The stabilizers tested were xanthan gum, propylene glycol alginate (PGA), a xanthan gum/guar gum/sodium alginate blend, a viscosifying modified corn starch, an emulsifying modified corn starch, microcrystalline cellulose (MCC), liquid salted egg yolks, liquid salted whole eggs, and dried egg whites (DEW). The emulsions were made with a laboratory high shear disperser and evaluated over 8 weeks by measurement of creaming in 100- mL graduated cylinders and by change in viscosity as measured by a Brookfield viscometer. The stabilizers and concentrations most effective at preventing separation and maintaining viscosity were MCC at 1%, 2%, and 3% in the 60% oil emulsion and 0.25% xanthan gum in the 70% oil emulsion. Average viscosities ranged from 3300 - 23,400 centipoise (cP). The emulsifying starch and dried egg whites were also effective at preventing creaming, but failed to maintain viscosity. The other ingredients showed some initial emulsion stability followed by either a gradual or sudden decrease in stabilization, as seen by decreasing viscosity and eventual separation.
Keywords: Oil-in-water emulsion; Emulsion stability; Dressing; Food Science (0359)